Hardware implementation of safety smart password based GSM module controlling circuit breaker - Shriwastava, Rakesh G.; Tapre, Pawan C.; Rewatkar, Rajendra M.; Choudhary, Swapna M.; Rathod, Ramesh K.; Mankar, Sham H.; Patil, Hemant R. Bhagat; Chavan, Salim A. (International Journal of Applied Power Engineering (IJAPE), 2025)
This research work highlights the hardware implementation of safety smart password-based GSM module controlling circuit breaker. Safety is the major concern in daily life for domestic activities. In current scenario, accidental death of a lineman are the major issues and to protect operators for the same. To control circuit breakers, passwords security is essential for lineman. Due to that electrical accident’s ratio is increased day to day life at the time of repairing the lines. It is also done due to lack of communication and coordination between maintenance and substation. For safety of lineman, on and off line turning operation is proposed. Secure password is for breaker operation and maintenance. In the proposed system, password is sent to the line operator's mobile phone and GSM module by automatic voltage regulator (AVR) microcontroller. Entered password and password received by the GSM receiver is match so circuit breaker will be smoothly operated. If password is incorrect, message will appear on the LCD display for security purposed and message sent to control room regarding unauthorized access to the system.